Monitoring spatiotemporal changes in global change drivers and their effects on semiarid woodlands and forests - fieldwork protocol [version 2; peer review: 2 approved] - Alice Nunes; Helena C. Serrano; Pedro Pinho; Adriana Principe; Juliana Monteiro; Silvana Munzi; Mana Gharun; Rocío Alonso; Rossella Guerrieri; Cristina Branquinho; Sami Ullah; Bernardo Rocha; et al. (Open Research Europe)
Training schools play a vital role in COST actions, particularly for young researchers, as they provide opportunities to visit international laboratories and learn new methodologies. In May 2024, CLEANFOREST organized its first training school, Monitoring Spatiotemporal Changes in Global Change Drivers and Their Effects on Semiarid Woodlands and Forests, held at the Faculty of Science of the Universidade de Lisboa. The training school included a field trip designed to explore global change drivers and their impacts on semiarid woodlands and forests. Participants engaged in hands-on activities to understand how forest ecosystems interact with key global change factors such as air quality and climate change. They were introduced to various monitoring techniques and parameters for assessing forest health, including ecosystem fluxes, tree physiology, mortality, and regeneration. Additionally, participants examined plant biodiversity and functional ecology, focusing on lichens and their connection to air quality, and soil physico-chemical properties. Participants applied these methodologies in real-world scenarios, conducting measurements (forest structure assessment, lichen diversity sampling, shrub and herbaceous diversity estimation, deadwood measurement and soil physico-chemical analysis) in different grazing management settings to assess their effects on tree growth, biodiversity, and soil properties. After the practical experience in the field using these experiences, participants were divided into groups to analyze and discuss collected data together with trainers. Key findings were summarized in presentations, together with main take home messages and suggestions on further questions to be explored and related attributes to monitor. This paper presents the field trip protocol used at Companhia das Lezírias, where simplified versions of established methodologies for sampling various ecosystem components were employed. The protocol provides a valuable reference for replicating similar studies, ensuring consistency in methodologies for future training activities.